Creative industries in Colombia: characterization and development (2012)
In Colombia the creative industries sector had not been researched in a systematic way. There are very few studies on the contribution that the sector has in the GDP, or in the number of jobs generated, or in the significance of the sector as a knowledge producer or in the effect it has in the expression of the local culture or in the manifestation of the creativity of the citizens of those countries. This paper shows a first characterization of the sector in Colombia, considering the perspectives and perception of two groups of stakeholders: the entrepreneurs and high level managers of companies in the creative industries sector and the national experts on the sector. The results allow a first characterization in different variables, not only for the Entrepreneurs/ high mangers in charge of the enterprises, but also from the business operations. Some policy recommendations are made to foster the development of this economic sector